On the Nature of Capital: Investment, Intangible Assets, and the Pecuniary Magnate - Veblen, Thorstein (Quarterly Journal of Economics, 1908)
Introductory summary, 104.—Certain effects of investment and the price system, 105.—Intangible assets, their nature, derivation, and basis, 111.—Summary of analysis of assets, 115.—Tangible and intangible assets distinct, but mutually convertible, 116.—Dependence of all assets on industrial production, 122.—Non-capitalizable income from assets, 125.—Place and function of the "Pecuniary Magnate, " 126.—"Timeless" gains from the use of (large) capital, 130.—Source of such "timeless" gains, 132.—Consequences for ordinary business men and ordinary profits, 135.